2015
DOI: 10.1371/journal.pone.0140825
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Devices as Effective Control Methods in Acupuncture Clinical Trials: A Systematic Review

Abstract: While the use of acupuncture has been recognised by the World Health Organisation, its efficacy for many of the common clinical conditions is still undergoing validation through randomised controlled trials (RCTs). A credible placebo control for such RCTs to enable meaningful evaluation of its efficacy is to be established. While several non-penetrating acupuncture placebo devices, namely the Streitberger, the Park and the Takakura Devices, have been developed and used in RCTs, their suitability as inert place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 65 publications
(129 reference statements)
2
104
0
Order By: Relevance
“…1 Further, for study Ib (see table 1), 3 Moroz et al reported the BIs of patients calculated from the number of subjects who did, or did not, experience the sensation of skin penetration, 2 which differed from the BIs calculated from the number of correct and incorrect guesses, even though we reported that "none of the subjects commented in the questionnaire that they had received a non-penetrating needle". 3 The patient BIs for study Ib 3 reported by Moroz et al were not appropriate.…”
mentioning
confidence: 58%
“…1 Further, for study Ib (see table 1), 3 Moroz et al reported the BIs of patients calculated from the number of subjects who did, or did not, experience the sensation of skin penetration, 2 which differed from the BIs calculated from the number of correct and incorrect guesses, even though we reported that "none of the subjects commented in the questionnaire that they had received a non-penetrating needle". 3 The patient BIs for study Ib 3 reported by Moroz et al were not appropriate.…”
mentioning
confidence: 58%
“…39 The findings from efficacy RCT comparing acupuncture and sham acupuncture may be partially explained by data suggesting that these devices may not be inert 40 and that some activity may arise from sensory and psycho-social cues. 39 The findings from efficacy RCT comparing acupuncture and sham acupuncture may be partially explained by data suggesting that these devices may not be inert 40 and that some activity may arise from sensory and psycho-social cues.…”
Section: Treatmentmentioning
confidence: 99%
“…For the sake of argument, discussion of the role of placebo is controversial as there is increasing evidence that acupuncture trials have been unable to control for placebo effects and thus, we cannot realistically measure the magnitude of the placebo effect [14,30]. Furthermore, there is evidence to suggest that efforts to control for placebo effects have accidentally biased against acupuncture [31,32].…”
Section: Mechanismsmentioning
confidence: 99%